Molecular interaction of hexylene glycol with toluene, aniline, chlorobenzene, nitrobenzene, benzaldehyde and N, N-dimethylaniline at 308.15 and 318.15 K. (3rd July 2020) - Prabhu, P.; Venis, A. Rose
ABSTRACT: Densities, viscosities and ultrasonic velocities of binary liquid mixtures of hexylene glycol (2-methyl-2, 4-pentanediol) with toluene, aniline, chlorobenzene, nitrobenzene, benzaldehyde and N, N -dimethylaniline have been measured at 308.15 and 318.15 K. From these data, excess volume ( V E ), deviation in isentropic compressibility (∆ KS ), deviation in viscosity (∆ η ), intermolecular free length (∆ Lf ), intermolecular free volume (∆ Vf ) and deviation in acoustic impedance (∆ Z ) have been calculated. FT-IR studied for appropriate mixture to conform hydrogen bonding. Thermodynamic excess properties have been correlated with the Redlich and Kister type of polynomial equation to derive the coefficients and standard errors. Variations in the calculated excess quantities have been studied for mixtures of hexylene glycol with component liquids. Intermolecular interactions have been interpreted from the obtaining experimental results.